Sykepleiestudenters læringsutbytte belyst gjennom to kunnskapsbaserte samarbeidsprosjekter. Fagutviklingsarbeid med studenter i hjemmesykepleiepraksis - Bjørsland, Bente; Hov, Reidun (Nordisk Tidsskrift for Helseforskning, 2015)
Health services are constantly met by greater demands on offering the best treatment and care based on quality and research. For that reason health workers and teachers in health care institutions and universities are working evidence-based. Hedmark University College and Hamar municipality have collaborated in two projects. The aim of this article is to illuminate the students’ learning outcomes in palliative care after participated in two evidence-based projects. Different written guides for conversations with patients, next of kin and staff, a log-book and an evaluation form were developed. Results show that the students learned about the significance of continuity in patients’ pain relief, spiritual and existential needs, and about palliative care in the municipality. The students concluded that they in some areas experienced greater learning outcomes from working with evidence-based practice than in their ordinary practice in the municipality.